Adolescent and parent experiences with Tele-Active Rehabilitation for concussion: an exploratory qualitative study. (29th July 2022) - Shore, Josh; Bernick, Alana; Nalder, Emily; Hutchison, Michael; Reed, Nick; Hunt, Anne
ABSTRACT: Purpose: To explore the experiences of adolescents with concussion and their parents who participated in a novel remotely delivered Tele-Active Rehabilitation (Tele-AR) intervention involving sub-symptom threshold exercise, education, and support. Specifically, we aimed to elicit perspectives regarding the remote delivery approach, valued aspects of the program, and perceived benefits of the intervention. Methods: This qualitative study took place within the context of a larger mixed-methods project exploring the feasibility of the Tele-AR intervention. A descriptive qualitative design was utilized. Semi-structured interviews were conducted with adolescents (n = 3; ages 14–17 years) with concussion and one of their parents (n = 3) within one week of completing the six-week Tele-AR intervention. Data were analyzed using thematic analysis. Results: Four themes were identified that capture participant experiences in the intervention: (1) Enabling access to active rehabilitation; (2) Focusing on individual needs; (3) Learning to take responsibility for recovery; and (4) Convenience and comfort of engaging in rehabilitation from home. Conclusions: A small sample of 3 adolescents with concussion and their parents were satisfied with the Tele-AR intervention and appreciated the convenience and comfort of engaging in rehabilitation from home, which facilitated adolescents taking responsibility for their own recovery. Findings support continued study of Tele-AR, which may be an accessible intervention to facilitate recovery in adolescents with concussion.